Remembering Chris Whelan (1947-2022) - Fahey, Tony; Nolan, Brian (The Economic and Social Review, 2025)
Christopher T. Whelan, Chris to his colleagues and friends, made major contributions to the study of social stratification, the development of sociology in Ireland, and to building European social science research collaboration